Penguatan Literasi, Numerasi, dan Identitas Budaya Anak Pekerja Migran Indonesia (PMI) melalui Pop-Up Book Nusantara - Eko Andy Purnomo; Dodi Mulyadi; Heri Dwi Santoso; Andari Puji Astuti; Muhammad Arif Zakyuddin (PT. Willy Print Art, 2025)
Abstract: Children of Indonesian migrant workers in Malaysia often learn in non-formal learning centres that operate with limited learning media and opportunities for culturally responsive literacy activities. This community service programme partnered with Sekolah Indonesia Kuala Lumpur (SIKL) to strengthen basic literacy and numeracy while nurturing cultural identity through interactive Pop-Up Books themed around Indonesian archipelagic culture. The programme was implemented in two days and involved 17 learners from Calistung and upper primary classes, assisted by teachers. Activities combined interactive read-aloud and storytelling, bilingual (Indonesian–English) storytelling practice, and guided hands-on workshops on creating simple Pop-Up mechanisms that can be reused as classroom media. Programme evaluation used descriptive observation, short reflection interviews, and product/performance review during reading and making sessions. Results indicate high learner engagement, increased participation in reading aloud, better recall of vocabulary and story content, and improved confidence in basic counting tasks embedded in the stories. Teachers reported gaining practical ideas for integrating Pop-Up media into their routine lessons. The programme concludes that Pop-Up book–based storytelling is feasible and attractive for learning centres abroad and can be scaled through continuous teacher mentoring and locally relevant story collections.